EFL Learners’ Experiences of Using E-Learning in an English Course - Nur Maulida Ifkarina; Ahmad Ridho Rojabi (JET ADI BUANA, 2023)
Due to its flexibility, online instruction has become the new normal in education. Utilizing various digital tools, learners can engage in online learning activities. One of the e-learning platforms is asynchronous e-learning for Madrasah, which provides a flexible and engaging learning environment. This study aimed to explore the experiences and motivations of EFL learners who used E-learning in an English course. This qualitative case study used observation, interviews, and document review.  A purposeful sampling technique was used to recruit 15 students to participate. The data was validated using triangulation of methods and data sources. EFL learners' experiences with E-learning in English subjects were classified into five categories: (1) course information access, (2) Autonomous learning, (3) Adaptation to technology, 4) Web-based learning system, and (5) Technical support. Furthermore, the motivations of EFL learners to use e-learning in an English course can be categorized into two groups: (1) Intrinsic motivation and (2) Extrinsic motivation. Pedagogically, e-learning has provided new experiences for students; therefore, e-learning should be adopted in this new normal era.